Antimalarial artemisinin-based combination therapies (ACT) and COVID-19 in Africa: In vitro inhibition of SARS-CoV-2 replication by mefloquine-artesunate. (October 2020) - Gendrot, Mathieu; Duflot, Isabelle; Boxberger, Manon; Delandre, Océane; Jardot, Priscilla; Le Bideau, Marion; Andreani, Julien; Fonta, Isabelle; Mosnier, Joel; Rolland, Clara; Hutter, Sébastien; La Scola, Bernard; et al.
ABSTRACT: Objectives: At the end of November 2019, a novel coronavirus responsible for respiratory tract infections (COVID-19) emerged in China. Despite drastic containment measures, this virus, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spread in Asia and Europe. The pandemic is ongoing with a particular hotspot in Southern Europe and America; many studies predicted a similar epidemic in Africa, as is currently seen in Europe and the United States of America. However, reported data have not confirmed these predictions. One of the hypotheses that could explain the later emergence and spread of COVID-19 pandemic in African countries is the use of antimalarial drugs to treat malaria, and specifically, artemisinin-based combination therapy (ACT). Methods: The antiviral activity of fixed concentrations of ACT at concentrations consistent with those observed in human plasma when ACT is administered at oral doses for uncomplicated malaria treatment was evaluated in vitro against a clinically isolated SARS-CoV-2 strain (IHUMI-3) in Vero E6 cells. Results: Mefloquine-artesunate exerted the highest antiviral activity with % inhibition of 72.1 ± 18.3 % at expected maximum blood concentration (Cmax ) for each ACT drug at doses commonly administered in malaria treatment. All the other combinations, artesunate-amodiaquine, artemether-lumefantrine, artesunate-pyronaridine, or dihydroartemisinin-piperaquine, showed antiviral inhibition in the same ranges (27.1 to 34.1 %). Conclusions: Antimalarial drugs for which concentration data in the lungs are available are concentrated from 10 to 160 fold more in the lungs than in blood. These in vitro results reinforce the hypothesis that antimalarial drugs could be effective as an anti-COVID-19 treatment.